Synthesis of 3-Aryl-1-aminopropane Derivatives: Lithiation–Borylation–Ring-Opening of Azetidinium Ions - Casoni, Giorgia; Myers, Eddie L.; Aggarwal, Varinder K. (Synthesis, 2016)
In situ generated 2-phenyl-azetidinium ylides react with boronic esters to form acyclic γ-dimethylamino tertiary boronic esters. The transformation is believed to involve the formation of a zwitterionic boronate, which subsequently undergoes ring-opening 1,2-migration, which is promoted by the relief of ring strain. Owing to the configurational instability of the initially formed ylides, which appear to be in equilibrium with the open-chain carbene form, the reaction is not stereospecific. The C–B bond of the γ-dimethylamino tertiary boronic esters can be transformed into a variety of functional groups (C–OH, C–vinyl, C–H, C–BF3), thus giving a diverse selection of 3-aryl-1-aminopropanes, which represent a privileged motif among drug molecules.
Keywords: 3-aryl-1-aminopropanes; azetidinium ion; lithiation; borylation; ring-opening; boronic esters